Pengaruh Pengawasan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Sekretariat Komisi Pemilihan Umum Kabupaten Lahat - Markus (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
The purpose of this research is to know the Influence of Supervision and Work Environment to Employee Performance of Secretariat Office of Election Commission of Lahat Regency. The respondents were all employees of the secretariat office of Lahat district electoral commission as much as 33 respondents. The analysis used is Multiple Linear Regression Analysis with hypothesis testing with t-test and F-test. From the value of regression equation obtained value equation Performance = 5.673 + 0.107 Supervision + 0.766 Work Environment + e. Monitoring and work environment variables together affect the performance with the value of determination coefficient of 67.4%. This means that 67.4% of the performance of the Lahat Regency Electoral Commission (KPU) is influenced by supervision and work environment while 32.6% is influenced by other factors outside the model. The result of partial test shows that the control variable has no significant effect on the performance, while the work environment variable has a significant positive effect on the performance.